Ecofreindly, candle precursor (Paraffin wax) production by Iranian indigenous bacterium to reduce the indoor health risks - Sadat Tabatabaee, Mitra (Archives of Advances in Biosciences, 2015)
The potential indoor air impacts of burning candles have drawn increased attention in recent years. Burning paraffin waxes itself, regardless to wick and the essence, produce some allergens and even carcinogenic compounds. Further biorefining of petroleum paraffin wax with proper bacteria is one of the proposed resolutions to decrease the health threat. Therefore in this study Iranian heavy crude oil sample were screened for the best isolate to reach the target. Manual culture and plate count method and screening were done in MSM medium supplemented with paraffin wax as the sole source of carbon and energy in 40°C and 150rpm. The growth curve of the best isolate was depicted through spectrophotometry during 24 hours. Then the isolate was characterized by biochemical test and molecular identification using 16srRNA. The spore forming, biosurfactant producing bacterium was identified as Bacillus cereus. Gas chromatogaraphs revealed the efficient degradation of long chain paraffin wax with the selected Bacillus cereus into 15 to 25 carbon length n- alkanes. The high physicochemical endurance of this bacterium including salinity tolerance from 0.5to 15 percent, pH from 4 to 10 and temperature growth range from 40 to 65°C, makes it a decent choice for industrial and environmental approaches.